Analysis of clinical characteristics and risk factors for patients with heat stroke in western China in 2022: a multicenter retrospective study - Zheng, Xin; Gao, Yuchun; Xie, Qinli; Chen, Qiulan; Guo, Chuan; Dong, Qionglan; Tang, Jin; Luo, Jun; Ge, Ying; He, Jian; Hou, Xiaolin; Zhou, Guanghong; et al. (Frontiers in Medicine, 2025)
ObjectivesTo analyzed the clinical characteristics and treatment modalities of heat stroke (HS) and to identify risk factors for a poor prognosis of HS and provide reference suggestions for its treatment and prevention.Measurements and main resultsWe enrolled a total of 247 patients, with hypertension, diabetes, and psychosis being the top three comorbidities associated with HS. The incidence of HS was higher among males and older individuals. Compared to the control group, the poor prognosis group experienced higher temperatures, a higher incidence of cerebral edema, and gastrointestinal bleeding (all p < 0.05). The poor prognosis group had significantly higher blood pH, HCO3-, Lac, Scr, AST, ALT, DBIL, CKMB, PT, DD, and PLT (all p < 0.05). Furthermore, logistic regression analysis revealed that Lac, Scr, and APACHE II were risk factors for poor prognosis (p < 0.05). The AUC values for the combined diagnostic model were 0.848 (95% CI: 0.781–0.914). Male morbidity, the number of patients with combined hypertension, the prognosis, and the APACHE II score and ALT level were all greater (p < 0.05) in the CHS group. The Kaplan–Meier analysis revealed that the CHS group had a significantly higher mortality rate than the EHS group.ConclusionA high incidence of hypertension, diabetes, psychosis, men, and older persons may be associated with HS. HS patients with high blood cell counts, impaired coagulation, liver and kidney diseases, and those with a specific type of CHS may face a poor prognosis. In patients with heart failure, APACHE II, Lac, and Scr were independent risk factors for a poor prognosis.